2009
DOI: 10.1089/fpd.2008.0134
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Drug Resistance and Molecular Characterization ofSalmonellaIsolated from Domestic Animals, Humans, and Meat Products

Abstract: Salmonella Typhimurium was the predominant serotype in both humans (13.4%) and domestic animals (34.3%), followed by Newport in animals (2.6%) and human (3.9%). Salmonella Arizona (0.7%), Salmonella Give (0.9%), and Salmonella Muenster (3.5%) were isolated from sick or dead animals. PFGE results confirmed occurrence of similar Salmonella genotypes in both domestic animals and humans. AMR profiles showed that most animal strains were multidrug resistant. A single human isolate had PFGE and multidrug resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 84 publications
(144 reference statements)
6
22
0
1
Order By: Relevance
“…Salmonella isolated from pork samples were commonly resistant to tetracycline, ampicillin, and streptomycin, as was in those isolated from chicken, which were additionally resistant to nalidixic acid. High resistance to those antimicrobial drugs were consistent to previous observations from various countries (16)(17)(18), which implies that the wide consumption of such antimicrobials as feed additives in livestocks contributes to emergence and dissemination of resistance in Salmonella. In addition, it had also been reported the sub-therapeutic doses of antimicrobial drugs in animal husbandry as a responsible factor in emergence and maintenance of multiple antimicrobial resistant pathogenic bacteria (19)(20)(21).…”
Section: Discussionsupporting
confidence: 89%
“…Salmonella isolated from pork samples were commonly resistant to tetracycline, ampicillin, and streptomycin, as was in those isolated from chicken, which were additionally resistant to nalidixic acid. High resistance to those antimicrobial drugs were consistent to previous observations from various countries (16)(17)(18), which implies that the wide consumption of such antimicrobials as feed additives in livestocks contributes to emergence and dissemination of resistance in Salmonella. In addition, it had also been reported the sub-therapeutic doses of antimicrobial drugs in animal husbandry as a responsible factor in emergence and maintenance of multiple antimicrobial resistant pathogenic bacteria (19)(20)(21).…”
Section: Discussionsupporting
confidence: 89%
“…Isolation of S. Typhimurium vars Copenhagen as the major Salmonella serovar 95% of the time supports previous reports of the existence of common genotypes circulating among the steers. This similarity in clonal relationship and antimicrobial resistance of S. Typhimurium vars Copenhagen was reported in a study that characterized Salmonella isolates from feedlot cattle (Khaitsa et al, 2007a), humans, and ready to eat turkey produce (Oloya et al, , 2009). This could possibly be responsible for the spread of such resistant genes among bacteria, a characteristic typical of gram negative bacteria.…”
Section: Salmonella From Animals 411 Salmonella In Feedlot Cattlesupporting
confidence: 58%
“…Another study (NARMS-EB, 2003) Tabe et al (2010a), reported widespread AMR among the Salmonella isolated; all but two of the Salmonella isolates were resistant to more than two of the antimicrobials tested with 96.6% of the isolates showing multidrug resistant antibiograms. The widespread AMR of Salmonella isolated from cattle in North Dakota had been reported before (Oloya, et al, 2009) with most animal strains showing more multidrug resistance compared to human Salmonella isolates possibly due to a difference in antimicrobial selection pressure exerted to the microorganisms in the two populations. Isolation of S. Typhimurium vars Copenhagen as the major Salmonella serovar 95% of the time supports previous reports of the existence of common genotypes circulating among the steers.…”
Section: Salmonella From Animals 411 Salmonella In Feedlot Cattlementioning
confidence: 84%
“…Differences in antimicrobial resistance prevalence between isolates from humans and animals were not formally tested in that study though, and resistance prevalence was highest among environmental samples. Somewhat higher resistance prevalence among animal than human Salmonella serotype Typhimurium isolates for some antimicrobial drugs has also been reported in other studies, and a role of cattle and other domestic animals as reservoir for human infection with multidrug-resistant Salmonella serotype Typhimurium strains has been proposed repeatedly (12,13,51,52).…”
Section: Discussionmentioning
confidence: 62%